2006
DOI: 10.1002/ange.200503575
|View full text |Cite
|
Sign up to set email alerts
|

A Subtle End‐Group Effect on Macroscopic Physical Gelation of Triblock Copolymer Aqueous Solutions

Abstract: En„d“scheidend: Alkyl‐Endgruppen können in einer solartigen Suspension einen thermoreversiblen Sol‐Gel‐Übergang auslösen, indem sie das makroskopische Selbstorganisationsverhalten beeinflussen. Das Bild zeigt PLGA‐PEG‐PLGA‐Triblockcopolymer/Wasser‐Mischungen in Sol‐ (Polymer a), Gel‐ (Polymere b und c) und Entmischungszuständen (Polymer d). PLGA=Poly(milchsäure‐co‐glycolsäure), PEG=Polyethylenglycol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…1, C and D) (17, 18). Specifically, we decorated the ends of P407 with an aliphatic polyphosphoester (PPE), one of a class of generally biocompatible and biodegradable polymers (17, 19).…”
Section: Resultsmentioning
confidence: 99%
“…1, C and D) (17, 18). Specifically, we decorated the ends of P407 with an aliphatic polyphosphoester (PPE), one of a class of generally biocompatible and biodegradable polymers (17, 19).…”
Section: Resultsmentioning
confidence: 99%
“…Aqueous PLGA–PEG–PLGA solutions with 1/1 weight mix ratio of copolymer‐1/copolymer‐2 were prepared via dissolving polymer in deionized water. The viscosity measurements of aqueous polymer solutions as a function of temperature were carried out on a strain‐controlled rheometer (ARES Rheolometric Scientific) using a Couette cell (Couette diameter, 32.0 and 34.0 mm; height 33.3 mm) . The measurements were operated with an oscillatory frequency of 10 rad/s and a heating rate of 0.5°C/min between 20°C and 45°C.…”
Section: Methodsmentioning
confidence: 99%
“…carried out on a strain-controlled rheometer (ARES Rheolometric Scientific) using a Couette cell (Couette diameter, 32.0 and 34.0 mm; height 33.3 mm). 34 The measurements were operated with an oscillatory frequency of 10 rad/s and a heating rate of 0.5 • C/min between 20 • C and 45 • C.…”
Section: Viscosity Measurements Of Polymer Solutions and Hydrogelsmentioning
confidence: 99%
“…Moreover, the sol-gel transition temperature and degradation properties can be adjusted by the polymer concentration, molecular weight of poly(ethylene oxide) and the lactic acid/glycolic acid ratio in the poly(lactic acid-coglycolic acid) blocks. In another study, Ding et al reported that the end groups have a surprising effect on the hydrogel formation (L. Yu et al, 2006). The results showed that the transition temperature increased with a decreasing hydrophobicity of the end groups.…”
Section: Hydrophobic Interactionmentioning
confidence: 96%